Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases